Mathematical Representation Ability of XI Grade Students of Vocational High School (SMK) in Connected Mathematics Project with Schoology Based on Student’ Independence (Universitas Negeri Semarang, 2022)
The present study aimed to describe the mathematical representation ability of vocational high school (SMK) students based on students’ autonomy. This research applied a mixed method with concurrent embedded design. The subject was accounting, and institution students grade XI of SMK N 2 Pekalongan 2020/ 2021 academic year. The result showed high self-reliance students achieved three ability aspects in mathematizing representing ability. The medium students’ ability created and used the representation to organize, take a note, communicate, and mathematize ideas. However, the two other aspects got ample category. The low students’ ability was not able to choose, apply, and represent the material to solve the problem, while the two other aspects were categorized as capable.